Mobile autonomy : exercises in artists' self-organization - Dockx, Nico; Gielen, Pascal; Reijnen, Leo.; Dog Republic (Amsterdam : Valiz, 2015)
Neoliberalism has taken autonomous professional values and labour firmly in its grasp. Traditional forms of employment are replaced with post-Fordist conditions in which work has become freelance, flexible, mobile, project-based, hybrid and temporary. This way of working is not new to artists. They have seen themselves confronted with these precarious conditions since many years. Mobile Autonomy detects what modes of economy and different innovative working modalities artists and other artistic professionals have developed in order to create their work in today’s social, economic and political conditions. Theoretical insights are alternated with hands-on practices, examples and art works in order to learn from and reflect on contemporary artists' working conditions.
boek